2014
DOI: 10.1002/chem.201304110
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Chiriquitoxin, an Analogue of Tetrodotoxin Isolated from the Skin of a Dart Frog

Abstract: The first total synthesis of chiriquitoxin, the most structurally complex analogue of tetrodotoxin isolated from a Costa Rican dart frog, has been accomplished from a newly designed intermediate for a variety of tetrodotoxin derivatives. The synthesis includes the third total synthesis of tetrodotoxin in this laboratory, and its intermediate was transformed into chiriquitoxin by a stereocontrolled aldol reaction with a D-camphor-derived lactone for installation of the unique side chain, and a new deprotection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
0
24
0
3
Order By: Relevance
“…TTX (1) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), CHTX (2) (Adachi et al, 2014a), 8-deoxyTTX (3) (Satake et al, 2014), 4,9-anhydroTTX (4) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), 4,9-anhydroCHTX (5), 4,9-anhydro-8-deoxyTTX (6), 5-deoxyTTX (7) (Satake et al, 2014), 5,11-dideoxyTTX (8) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013), 5,6,11-trideoxyTTX (9) (Adachi et al, 2014b), 4,9-anhydro-5-deoxyTTX (10) (Satake et al, 2014), 4,9-anhydro-5,11-dideoxyTTX (11) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013) and 4,9-anhydro-5,6,11-trideoxyTTX (12) (Adachi et al, 2014b) were synthesized as reported in the literature (Figure 1 KOD-Plus, T4 ligase and the In-Fusion HD Cloning kit were purchased from Takara Bio, Inc. (Kusatsu, Shiga, Japan). PCR primers were purchased from Fasmac Co., Ltd. (Atsugi, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…TTX (1) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), CHTX (2) (Adachi et al, 2014a), 8-deoxyTTX (3) (Satake et al, 2014), 4,9-anhydroTTX (4) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), 4,9-anhydroCHTX (5), 4,9-anhydro-8-deoxyTTX (6), 5-deoxyTTX (7) (Satake et al, 2014), 5,11-dideoxyTTX (8) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013), 5,6,11-trideoxyTTX (9) (Adachi et al, 2014b), 4,9-anhydro-5-deoxyTTX (10) (Satake et al, 2014), 4,9-anhydro-5,11-dideoxyTTX (11) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013) and 4,9-anhydro-5,6,11-trideoxyTTX (12) (Adachi et al, 2014b) were synthesized as reported in the literature (Figure 1 KOD-Plus, T4 ligase and the In-Fusion HD Cloning kit were purchased from Takara Bio, Inc. (Kusatsu, Shiga, Japan). PCR primers were purchased from Fasmac Co., Ltd. (Atsugi, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…21 As these amino protecting groups could be easily removed under each specific condition, this protecting-group transScheme 10 New guanidine synthesis used in the total synthesis of 5, 11-dideoxytetrodotoxin (8) T. Nishikawa et al…”
Section: Protecting-group Transformation Of the N-trichloroacetyl Groupmentioning
confidence: 99%
“…Following these successes, they completed the synthesis of tetrodotoxin ( 3 ) in 2003, 281 reported an improved route in 2004, 283,284 and finished the synthesis of chiriquitoxin ( 194 ) in 2014. 287 …”
Section: The Saxitoxin/tetrodotoxin Alkaloidsmentioning
confidence: 99%